Pengaruh Cognitive Behaviour Therapy dalam Mencegah Risiko Bunuh Diri pada Siswa SMPN 2 Batu Sangkar - Alice Rosy; Budi Anna Keliat; Dewi Eka Putri (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Suicide cases in adolescents have increased from year to year. This study aimed to analyze the effect of cognitive behavioral therapy in preventing suicide risk in students at Batu Nangkar 2 Junior High School in 2015. CBT is a combination of cognitive therapy and behavioral therapy designed to change negative thought patterns into positive ones so as to produce changes in behavior. Research design was "Quasi Experimental Pre-Post with "Control Group". The study was conducted on 60 respondents, 30 people in the intervention group, 30 people in the control group. The intervention group was divided into 4 groups, CBT there were 5 sessions, sessions 1,2 and 3 were combined into 1 meeting, sessions 4 and 5 each had 1 meeting, with 30 minutes each session. The results showed a significant decrease in cognitive and behavioral responses about suicide (p-value≤0.05) in students who received Cognitive Behavior Therapy (CBT) recommended to be applied to students who had suicidal risk along with other nursing interventions. Keywords: suicide; prevention; cognitive behavior therapy ABSTRAK Kasus bunuh diri pada remaja mengalami peningkatan dari tahun ketahun. Penelitian ini bertujuan menganalisa pengaruh cognitif behavior terapi dalam mencegah risiko bunuh diri pada siswa SMP N 2 Batu Sangkar.tahun 2015. CBT merupakan gabungan dari terapi kognitif dan terapi perilaku yang dirancang untuk merubah pola pikir negatif menjadi positif sehingga menghasilkan perubahan pada perilaku. Desain penelitian “Quasi Esperimental Pre-Post With “Control Group”. Penelitian dilakukan terhadap 60 responden, 30 orang kelompok intervensi, 30 orang kelompok kontrol. Kelompok intervensi di bagi menjadi 4 kelompok, CBT ada 5 sesi, sesi 1,2 dan 3 digabung jadi 1 kali pertemuan, sesi 4 dan 5 masing masing 1 kali pertemuan, dengan waktu 30 menit setiap sesinya. Hasil penelitian menunjukkan penurunan dari respon kognitif dan perilaku tentang bunuh diri secara bermakna (P-value≤0,05) pada siswa yang mendapatkan Cognitive Behaviour Therapy (CBT) direkomendasikan untuk diterapkan pada siswa yang memiliki risiko bunuh diri bersama intervensi keperawatan lainnya. Kata kunci: bunuh diri; pencegahan; cognitive behavior therapy